2018
DOI: 10.1002/bjs.10735
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after hepatic resection

Abstract: This study confirmed overall good QoL in patients undergoing liver resection for benign or malignant tumours, which improved after surgery. Benign diseases were associated with better short- and long-term QoL scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…In this study, patients older than 40 years showed comparable overall PCS after the RF procedure compared to that of the general German control population. This is in contrast to HRQoL reports after HR, where HRQoL regularly shows an initial decline with considerable improvement after 6 months with the highest scores after 24 months 6 . According to Toro et al and Dasgupta et al 27 , 28 this pattern may be indicative of the regenerative capacity of the liver.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, patients older than 40 years showed comparable overall PCS after the RF procedure compared to that of the general German control population. This is in contrast to HRQoL reports after HR, where HRQoL regularly shows an initial decline with considerable improvement after 6 months with the highest scores after 24 months 6 . According to Toro et al and Dasgupta et al 27 , 28 this pattern may be indicative of the regenerative capacity of the liver.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding hepatic neoplasms, hepatic resection (HR) is considered to be the gold standard in the management of both primary and metastatic disease. However, HR is still associated with relatively high morbidity rates up to 59.9% 2 5 and with a corresponding initial decline in HRQoL after surgery 6 . Radiofrequency ablation (RF) affords more rapid post-procedure recovery and thus good post-procedure HRQoL by virtue of its minimally invasive nature, and has been increasingly accepted as an alternative in the management of primary or metastatic liver tumors 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Such a study enables researchers to identify areas of care that may need particular attention, while learning those to which patients may adapt naturally. Similar common human reactions were identified in the study of patients following hepatic resection, indicating that those with malignant and benign disease had similar QoL measurements. As the only treatment possible for survival, it would seem that the malignant group attuned themselves to the situation.…”
supporting
confidence: 64%
“…11 In recent years, more studies have started reporting QoL, recognizing its place as an important perioperative and longer term outcome measure. [12][13][14] Up until now there has been no systematic review or meta-analysis evaluating this subject.…”
Section: Introductionmentioning
confidence: 99%